ANALISIS PENGARUH INSTRUMEN PEMBAYARAN NON-TUNAI (APMK DAN UANG ELEKTRONIK) TERHADAP MONEY MULTIPLIER - Triajie, Reyne Amelia; Munawar Ismail (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The increasing use of non-cash payment instruments in Indonesia, such as Card Payment Instrument (APMK) and electronic money, shows public awareness and confidence in switching from cash. This has an impact on the money multiplier. The money multiplier plays an important role in the formation of money supply and monetary control. The stability of the money multiplier can provide greater opportunities for Bank Indonesia to implement policies effectively in influencing the supply of money in circulation so the ultimate goal of monetary aggregates can be achieved and a conducive atmosphere for the economy is created. This research aims to determine the influence of ATM+Debit card, credit card and electronic money variables on the money multiplier in Indonesia. In connection with this, the author uses the Error Correction Model (ECM) as an analysis method in this research. The research results show that the Card Payment Instrument (APMK) variable through the nominal transactions of ATM+Debit card and credit card and the nominal transactions of electronic money have significant positive effect on the value of the money multiplier in Indonesia in both the short and long term. It means when the nominal variable for ATM+Debit card, credit card, and electronic money transactions increases, the value of the money multiplier will also increase and vice versa. The increasing use of non-cash payment instruments in Indonesia, such as Card Payment Instrument (APMK) and electronic money, shows public awareness and confidence in switching from cash. This has an impact on the money multiplier. The money multiplier plays an important role in the formation of money supply and monetary control. The stability of the money multiplier can provide greater opportunities for Bank Indonesia to implement policies effectively in influencing the supply of money in circulation so the ultimate goal of monetary aggregates can be achieved and a conducive atmosphere for the economy is created. This research aims to determine the influence of ATM+Debit card, credit card and electronic money variables on the money multiplier in Indonesia. In connection with this, the author uses the Error Correction Model (ECM) as an analysis method in this research. The research results show that the Card Payment Instrument (APMK) variable through the nominal transactions of ATM+Debit card and credit card and the nominal transactions of electronic money have significant positive effect on the value of the money multiplier in Indonesia in both the short and long term. It means when the nominal variable for ATM+Debit card, credit card, and electronic money transactions increases, the value of the money multiplier will also increase and vice versa.